2014
DOI: 10.18632/genesandcancer.11
|View full text |Cite
|
Sign up to set email alerts
|

Internal ribosome entry site of bFGF is the target of thalidomide for IMiDs development in multiple myeloma

Abstract: Although new analogues of immunomodulatory drugs (IMiDs) are being developed for MM, the molecular mechanism of these drugs remains unclear. In the current study, we used MM cell lines as a model to investigate the molecular mechanism of thalidomide and to compare its potency with IMiDs such as pomalidomide. We determined that thalidomide did not inhibit cell proliferation of RPMI8226 and U266 MM cells, whereas pomalidomide showed a significant inhibitory effect on these two MM cell lines. Interestingly, we fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Pathway analysis suggested that the Ribosome pathway was upregulated by RA or THAL as sole treatments although the effect was reduced after combined treatment. On the other hand, it has been reported that in multiple myeloma cells internal ribosome entry site (IRES) of bFGF was inhibited at low concentration of THAL [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis suggested that the Ribosome pathway was upregulated by RA or THAL as sole treatments although the effect was reduced after combined treatment. On the other hand, it has been reported that in multiple myeloma cells internal ribosome entry site (IRES) of bFGF was inhibited at low concentration of THAL [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…IRESes have the potential to impact upon MM drug response. For example, thalidomide may reduce the proliferative effects of MM cells in part by targeting the IRES of the b-FGF growth factor ( 72 ).…”
Section: Multiple Myeloma As a Paradigm For The Importance Of Cap-indmentioning
confidence: 99%